2016
DOI: 10.1038/srep36674
|View full text |Cite
|
Sign up to set email alerts
|

Significant Phylogenetic Signal and Climate-Related Trends in Leaf Caloric Value from Tropical to Cold-Temperate Forests

Abstract: Leaf caloric value (LCV) is a useful index to represent the conversion efficiency of leaves for solar energy. We investigated the spatial pattern of LCV and explored the factors (phylogeny, climate, and soil) that influence them at a large scale by determining LCV standardized by leaf area in 920 plant species from nine forest communities along the 3700 km North-South Transect of Eastern China. LCV ranged from 0.024 to 1.056 kJ cm−2 with an average of 0.151 kJ cm−2. LCV declined linearly with increasing latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Cladogram of the plant families (modified from Song et al 2016) and species used in this study. Species from the tropical region are marked in red, species from the temperate region are in blue.…”
Section: Methodsmentioning
confidence: 99%
“…Cladogram of the plant families (modified from Song et al 2016) and species used in this study. Species from the tropical region are marked in red, species from the temperate region are in blue.…”
Section: Methodsmentioning
confidence: 99%
“…These nine forests span cold-temperate, temperate, subtropical, and tropical forests from 18.7 to 51.8 • N. The mean annual temperature (MAT) of these forests ranges from −4.4 to 20.9 • C, while mean annual precipitation (MAP) ranges from 481.6 to 2449.0 mm. Soils vary from tropical red soils with low organic matter to brown soils with high organic matter (Song et al, 2016). Detailed geographical information of the region is presented in Table S1.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Furthermore, chlorophyll content might be affected by community structure, because the With the development of the molecular clock theory (molecular evolution speed constancy) and fossil dating data, researchers found that phylogenic history play a decisive role for some plant traits (Comas et al, 2014;Kong et al, 2014;Li et al, 2015). Some plant traits (i.e., N and P content and calorific values) are strongly affected by the phylogeny of plant species (Stock and Verboom, 2012;Chen et al, 2013;Song et al, 2016). In contrast, in our study, although Chl in the overall and different life forms had significant phylogenetic signals, the phylogenetic signal K values were close to zero.…”
Section: Weak Increasing Latitudinal Pattern Of Chl In Natural Forestsmentioning
confidence: 99%
“…The energy utilization strategy of plants could also be pivotal, combined with the other physiological indicators, to assess the adaptability of plants to the environment [ 4 ]. The calorific value reflected the light utilization efficiency of plants and became an important indicator for measuring their physiological activities [ 5 ]. Studies have found that the composition, structure, and function of different plants as well as climate change influence differences in plant calorific values.…”
Section: Introductionmentioning
confidence: 99%